Protection of high-performance concrete on the durability of GFRP bars: Deterioration mechanism and tensile strength prediction - Yuan Yue; Wen-Wei Wang; Lei Zhang; Liang Liang; Qiang Zhao; Yuzhou Zheng (Case Studies in Construction Materials)
The objective of this study was to compare the impact of two commonly used high-performance concretes (HPC) on the durability of GFRP bars. A total of 279 GFRP specimens were manufactured and subjected to micro morphological analysis and mechanical property testing. The residual tensile strength of 270 specimens was assessed after 120 days of immersion. Concurrently, 9 specimens were chosen for microscopic to explore the degradation mechanism of GFRP bars. The experimental findings indicate that HPC can create more favorable environmental conditions for GFRP compared to normal concrete. After 120 days of exposure, slight color changes, minor alterations in microscopic images, and higher tensile strength retention were observed in the HPC environment. Furthermore, when combined with pH test results, it was discovered that HPC exhibits lower pore solution pH or compactness of porosity than normal concrete, which significantly reduces the penetration of corrosive substances and contributes to maintaining the durability of GFRP. Additionally, ECC surpasses UHPC in terms of durability protection, as the residual tensile strength (RS) of GFRP bars in ECC reaches 68.99 %, slightly higher than UHPC (66.32 %). A computational method is also proposed to address the incompatibility between multiple fitting and accelerated transformation in traditional prediction theory. This new method is implemented as a Matlab-based iterative algorithm grounded on the Arrhenius relationship, enabling automatic calculation and identification of solutions that satisfy multiple degradation-related conditions. It greatly reducing manual calculation burden while providing a practical tool for researchers to analyze accelerated material degradation.